The Impact of Armed Conflict on Environmental Damage and Children's Rights - Tendiyanto, Teten; Ramdhani, Zulmi; Abdullah, Abdullah (Universitas Kuningan, 2025)
Armed conflict, which is a manifestation of violence and hostility, is a cause of loss of life and material damage, having profound as well as long-lasting impacts on environment. Therefore, this study aimed to analyze how International Humanitarian Law (IHL) addresses environmental protection during armed conflict, with a particular focus on Israel–Palestine context. The analysis also examined how environmental damage affected rights of children. A normative legal method was used, relying on literature as well as existing legal instruments, conventions, and scientific interpretations. The results showed that IHL provided a legal framework to protect environment. Major instruments included Additional Protocol I of 1977 and Environmental Modification Convention of 1977, which prohibited methods of warfare causing widespread, long-term, and severe environmental damage. However, these legal norms are often weak in practice because enforcement was limited and there were no binding obligations for some states. In Israel–Palestine conflict, environmental damage resulting had destroyed ecological infrastructure, cutting off access to clean water, sanitation, health services, and educationm all basic rights protected under Convention on Rights of Child (CRC). Children were particularly vulnerable in this situation, facing higher risks of malnutrition, disease outbreaks, psychological trauma, as well as setbacks in survival and development. This study concluded that the gap between legal norms and practical enforcement undermined both environmental sustainability and the protection of rights of children. Strengthening international accountability mechanisms and improving global cooperation were recommended to make environmental protection during armed conflict a concrete and enforceable responsibility that safeguards future generations.